Metal-doped carbon nanofiber wave-absorbing material as well as preparation method and application thereof

The metal-doped carbon nanofiber absorbent material prepared by electrospinning method forms a composite material with a three-dimensional network structure through the combination of metal elements such as iron, cobalt and nickel, which solves the shortcomings of existing materials in terms of density, chemical stability and absorption performance, and achieves efficient electromagnetic wave absorption performance and good preparation conditions.

CN119877153AInactive Publication Date: 2025-04-25TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510362922.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing microwave absorbing materials have shortcomings in density, chemical stability and absorption properties, and it is difficult to meet the needs of high absorption strength, wide absorption bandwidth, low density and ultra-thin characteristics.

Method used

The metal-doped carbon nanofiber absorbent material is prepared by electrospinning method. By combining metal elements such as iron, cobalt and nickel with carbon nanofibers, a composite material with a three-dimensional network structure is formed, and the coupling effect of multiple loss mechanisms is achieved, thereby improving the absorbent performance.

Benefits of technology

It realizes the characteristics of "light, thin, wide and strong" wave absorbing material, has efficient electromagnetic wave absorption performance, and is safe in the preparation process, low in cost, and controllable product morphology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877153A_ABST
    Figure CN119877153A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-doped carbon nanofiber wave-absorbing material as well as a preparation method and application thereof, and belongs to the technical field of microwave-absorbing composite materials. The chemical formula of the metal-doped carbon nanofiber wave-absorbing material is # imgabs0 #, and 0 lt; nlt; 10. The preparation method comprises the following steps: mixing metal salts in proportion, adding into an organic solvent containing a high-molecular polymer, and uniformly stirring to obtain a precursor solution; spinning the precursor solution under different conditions by using an electrostatic spinning method to obtain precursor fibers, carrying out vacuum drying on the precursor fibers, and pre-oxidizing the precursor fibers in a drying oven to obtain a stable three-dimensional network fiber structure; and carrying out heat treatment on a product obtained by pre-oxidation in a nitrogen atmosphere to obtain the metal-doped carbon nanofiber material. The composite material provided by the invention has a three-dimensional network structure, the composition of the three metal elements of iron, cobalt and nickel exerts the coupling effect of various loss mechanisms, the characteristics of light weight, thinness, width and strength are met while the wave-absorbing performance is improved, the preparation conditions are controllable, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microwave absorbing composite materials, and in particular to a metal-doped carbon nanofiber absorbing material and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of communication technology, the demand for electromagnetic wave absorbing materials has been growing, especially those with high absorption intensity, wide absorption bandwidth, low density and ultra-thin characteristics. Although traditional metal materials are widely used, their disadvantages such as high density and poor chemical stability have prompted researchers to seek new alternative materials. Carbon-based materials have become the focus of research due to their light weight, excellent conductivity and chemical stability. They can not only be used alone, but also be compounded with magnetic materials to form magnetic carbon-based composites to improve impedance matching and microwave absorption performance.

[0003] The dielectric loss properties of carbon-based materials are relatively single, so by combining with magnetic materials such as iron, cobalt, nickel and their alloys, a composite absorber with multiple loss mechanisms can be constructed to achieve stronger wave absorption performance. This composite material not only reduces the overall density, but also enhances the oxidation resistance. Common carbon-based materials include carbon powder, graphite, carbon nanotubes and graphene, which are often compounded with magnetic alloys in practical applications to optimize impedance matching and loss characteristics.

[0004] In addition, the structural design of absorbent materials is also a research hotspot in the field of microwave absorption. One-dimensional magnetic structures, such as nanofibers, nanowires, nanochains, and nanotubes, have attracted attention due to their large aspect ratio, shape anisotropy, and high specific surface area. These one-dimensional structures help to form unique one-dimensional anisotropic magnetic interaction networks and interpenetrating conductive networks, thereby enhancing the expansion and interaction with the external electromagnetic field and effectively attenuating electromagnetic waves. One-dimensional structures can also regulate the distribution of micro-electric fields, improve the electromagnetic polarization effect, and increase the Snoek's limit, so that the magnetic resonance moves toward the high frequency direction, thereby being used as microwave absorbers in a wider frequency range.

[0005] As a new preparation method, electrospinning technology can adjust the composition and ratio of the precursor solution, rationally regulate the composition and structure of one-dimensional materials, and provide an effective way to develop one-dimensional magnetic electromagnetic wave absorbing materials with specific properties. These research advances not only promote the development of absorbing materials, but also provide new possibilities for the advancement of electromagnetic protection technology. Summary of the invention

[0006] The purpose of the present invention is to provide a metal-doped carbon nanofiber absorbing material and a preparation method and application thereof. The composite material has a three-dimensional network structure, and the composition of the three metal elements of iron, cobalt and nickel exerts a coupling effect of multiple loss mechanisms, improves the absorbing performance while meeting the characteristics of "light, thin, wide and strong", and at the same time meets the conditions of controllable preparation conditions and low cost.

[0007] To achieve the above object, the present invention provides a metal-doped carbon nanofiber absorbing material, characterized in that the chemical formula of the metal-doped carbon nanofiber absorbing material is: , where 0 <n<10。

[0008] Preferably, the maximum reflection loss of the metal-doped carbon nanofiber absorbing material is -10 to -60 dB, and the effective absorption bandwidth is 2 to 7 GHz.

[0009] Preferably, the metal-doped carbon nanofiber absorbing material has a nanoscale uniform three-dimensional conductive fiber network structure.

[0010] The present invention also provides a method for preparing the above-mentioned metal-doped carbon nanofiber absorbing material, comprising the following steps: S1, mixing metal salts in proportion, adding them into an organic solvent containing a high molecular weight polymer, and stirring them uniformly to obtain a precursor solution; S2, spinning the precursor solution by electrospinning to obtain precursor fibers; S3. The precursor fiber is vacuum dried and pre-oxidized in an oven to obtain a stable three-dimensional network fiber structure; the pre-oxidized product is heat-treated in a nitrogen atmosphere to obtain a metal-doped carbon nano-absorbing fiber material.

[0011] Preferably, in step S1, the metal salt is an iron salt, a cobalt salt and a nickel salt, the iron salt is any one of iron nitrate, iron carbonate and iron acetylacetonate, the cobalt salt is any one of cobalt nitrate, cobalt carbonate and cobalt acetylacetonate, the nickel salt is any one of nickel nitrate, nickel carbonate and nickel acetylacetonate, and the input molar ratio of the iron salt, the cobalt salt and the nickel salt is , where 0 <n<10; The high molecular polymer is any one of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol; and the organic solvent is N,N-dimethylformamide or tetrahydrofuran.

[0012] Preferably, in step S1, the mass ratio of the total mass of the metal salt to the high molecular weight polymer is (2-3.5):1; the mass ratio of the high molecular weight polymer to the organic solvent is (1-1.5):10.

[0013] Preferably, in step S2, the equipment parameters of the electrospinning method are: voltage intensity 15~20kV, injection rate 0.5ml / h, collector distance 5~15cm, temperature 30~50℃, maximum humidity 60~70%RH, minimum humidity 20~30%RH.

[0014] Preferably, in step S3, the vacuum drying temperature is 60-90° C., the insulation time is 8-18 h, the pre-oxidation temperature is 120-200° C., and the insulation time is 1-4 h.

[0015] Preferably, in step S3, the heat treatment temperature can be selected to be 700-900° C., and the insulation time can be selected to be 0.5-2 h.

[0016] The present invention also provides an application of a metal-doped carbon nanofiber absorbing material in an electromagnetic wave absorbing material.

[0017] Therefore, the present invention adopts the above-mentioned metal-doped carbon nanofiber absorbing material and its preparation method and application, which have the following beneficial effects: (1) The present invention adopts an electrospinning method to prepare a metal-doped carbon nanofiber composite absorbing material, which has safe operation, controllable product morphology, and low cost; (2) The ternary iron-cobalt-nickel alloy composite carbon nanofibers used in the present invention can adjust impedance matching, magnetic loss, etc. by changing the ratio of metal elements and the ratio of metal to carbon, thereby achieving effective attenuation of electromagnetic waves.

[0018] (3) The product of the present invention has the advantages of low filling rate, small fiber density and high absorption strength.

[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the XRD spectra of the products prepared in Examples 1 to 9; Figure 2 This is the electromagnetic wave absorption performance curve of the (FeCo)1Ni8 / C metal-doped carbon nanofiber prepared in Example 2; Figure 3 This is the electromagnetic wave absorption performance curve of the (FeCo)3Ni4 / C metal-doped carbon nanofiber prepared in Example 6; Figure 4 This is a SEM image of the product (FeCo)1Ni8 / C metal-doped carbon nanofibers prepared in Example 2. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0022] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0023] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0024] Embodiment 1 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo) 0.5 Ni9 / C, prepared by electrospinning and calcination: Step 1: Weigh 1.0 g of polyvinylpyrrolidone (PVP) K30 and 0.5 g of polyvinylpyrrolidone K88-96, dissolve in 10 ml of N,N-dimethylformamide (DMF), and heat and stir at 40°C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate, including 0.0005 mol Fe(NO3)3·9H2O, 0.0005 mol Co(NO3)2·6H2O and 0.009 mol Ni(NO3)2·6H2O, is weighed and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 30°C, the maximum humidity is 60% RH, the minimum humidity is 20% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 15 kV, and a distance of 5 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 60°C to dry for 18 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 120° C. forced air drying oven for pre-oxidation for 4 hours; Step 6: The pre-oxidized product obtained in step 4 is heated to 900°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept at this temperature for 0.5h, and then cooled to room temperature at a cooling rate of 2°C / min to obtain (FeCo) 0.5 Ni9 / C metal doped carbon nanofibers.

[0025] The (FeCo) prepared in this example 0.5Ni9 / C metal-doped carbon nanofibers were mixed with paraffin in a mass ratio of 3:7 and pressed into a ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a thickness of about 2 mm. The reflection loss test of the electromagnetic wave frequency band of 2~18 GHz was carried out using the coaxial line method of a vector network analyzer.

[0026] Embodiment 2 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo)1Ni8 / C, and it is prepared by electrospinning and calcining: Step 1: Weigh 1.0 g of polyvinylpyrrolidone K30 and 0.5 g of polyvinylpyrrolidone K88-96, dissolve in 10 ml of DMF, and heat and stir at 40°C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate, including 0.001 mol Fe(NO3)3·9H2O, 0.001 mol Co(NO3)2·6H2O and 0.008 mol Ni(NO3)2·6H2O, is weighed and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 40°C, the maximum humidity is 65% RH, the minimum humidity is 25% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 18 kV, and a distance of 10 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 80°C to dry for 12 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 150° C. forced air drying oven for pre-oxidation for 2 h; Step 6: Heat the pre-oxidation product obtained in step 4 to 800°C at a heating rate of 3°C / min under a nitrogen atmosphere and keep it at that temperature for 1 hour, and then cool it to room temperature at a cooling rate of 3°C / min to obtain (FeCo)1Ni8 / C metal-doped carbon nanofibers.

[0027] The (FeCo)1Ni8 / C metal-doped carbon nanofibers prepared in this embodiment were mixed with paraffin wax at a mass ratio of 3:7 and pressed into a ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a thickness of about 2 mm. The reflection loss test of the electromagnetic wave frequency band of 2-18 GHz was carried out using a vector network analyzer coaxial line method. Figure 2 As shown, in the thickness range of 0~5mm, the maximum reflection loss of (FeCo)1Ni8 / C metal-doped carbon nanofiber material in the frequency band of 2~18GHz is -40.2dB, and the effective absorption bandwidth can reach 5.84GHz, corresponding to a thickness of 2.7mm.

[0028] The samples prepared in this example were imaged by SEM, and the test results are as follows: Figure 4 As shown, the (FeCo)1Ni8 / C metal-doped carbon nanofiber material has a three-dimensional network structure, in which uniform alloy particles are doped on the carbon fiber network with a diameter of 150~200nm, and the alloy particle size is about 30~100nm.

[0029] Embodiment 3 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo) 1.5 Ni7 / C, prepared by electrospinning and calcination: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 1.0 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate is weighed, including 0.0015 mol Fe(NO3)3·9H2O, 0.0015 mol Co(NO3)2·6H2O and 0.007 mol Ni(NO3)2·6H2O, and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 50°C, the maximum humidity is 70% RH, the minimum humidity is 30% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 20 kV, and a distance of 15 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 90°C to dry for 8 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 200° C. forced air drying oven for pre-oxidation for 1 hour; Step 6: The pre-oxidized product obtained in step 4 was heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 2h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain (FeCo) 1.5 Ni7 / C metal doped carbon nanofibers.

[0030] Embodiment 4 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo)2Ni6 / C, and it is prepared by electrospinning and calcining: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 0.5 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate is weighed, including 0.002 mol Fe(NO3)3·9H2O, 0.002 mol Co(NO3)2·6H2O and 0.006 mol Ni(NO3)2·6H2O, and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 50°C, the maximum humidity is 60% RH, the minimum humidity is 20% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 20 kV, and a distance of 15 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 60°C to dry for 18 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 120° C. forced air drying oven for pre-oxidation for 4 hours; Step 6: Heat the pre-oxidation product obtained in step 4 to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and keep it warm for 0.5h, and then cool it to room temperature at a cooling rate of 3°C / min to obtain (FeCo)2Ni6 / C metal-doped carbon nanofibers.

[0031] The (FeCo)2Ni6 / C metal-doped carbon nanofibers prepared in this embodiment were mixed with paraffin in a mass ratio of 4:6 and pressed into a ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a thickness of about 2 mm. The reflection loss test of the electromagnetic wave frequency band 2~18 GHz was carried out using a vector network analyzer coaxial line method.

[0032] Embodiment 5 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo): 2.5 Ni5 / C, prepared by electrospinning and calcination: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 0.5 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate is weighed, including 0.0025 mol Fe(NO3)3·9H2O, 0.0025 mol Co(NO3)2·6H2O and 0.005 mol Ni(NO3)2·6H2O, and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 50°C, the maximum humidity is 60% RH, the minimum humidity is 20% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 20 kV, and a distance of 15 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 60°C to dry for 18 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 120° C. forced air drying oven for pre-oxidation for 4 hours; Step 6: The pre-oxidized product obtained in step 4 was heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 1h, and then cooled to room temperature at a cooling rate of 3°C / min to obtain (FeCo) 2.5 Ni5 / C metal doped carbon nanofibers.

[0033] Embodiment 6 The metal-doped carbon nanofiber absorbing composite material of this embodiment has a molecular formula of (FeCo)3Ni4 / C and is prepared by electrospinning and calcining: Step 1: Weigh 1.0 g of polyvinylpyrrolidone K30 and 0.5 g of polyvinylpyrrolidone K88-96, dissolve in 10 ml of DMF, and heat and stir at 40°C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate, including 0.003 mol Fe(NO3)3·9H2O, 0.003 mol Co(NO3)2·6H2O and 0.004 mol Ni(NO3)2·6H2O, is weighed and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 40°C, the maximum humidity is 65% RH, the minimum humidity is 25% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 15 kV, and a distance of 5 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 80°C to dry for 12 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 150° C. forced air drying oven for pre-oxidation for 2 h; Step 6: The pre-oxidized product obtained in step 4 was heated to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 2 hours, and then cooled to room temperature at a cooling rate of 2°C / min to obtain (FeCo)3Ni4 / C metal-doped carbon nanofibers. Figure 3As shown, in the thickness range of 0~5mm, the maximum reflection loss of (FeCo)3Ni4 / C metal-doped carbon nanofiber material in the frequency band of 2~18GHz is -54.1dB, and the effective absorption bandwidth is 2.64GHz, corresponding to a thickness of 3.5mm, of which the effective absorption bandwidth corresponding to 1.6mm can reach 6.72GHz.

[0034] Embodiment 7 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo): 3.5 Ni3 / C, prepared by electrospinning and calcination: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 1.0 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate is weighed, including 0.0035 mol Fe(NO3)3·9H2O, 0.0035 mol Co(NO3)2·6H2O and 0.003 mol Ni(NO3)2·6H2O, and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 45°C, the maximum humidity is 63% RH, the minimum humidity is 23% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 15 kV, and a distance of 10 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 70°C to dry for 15 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 180°C forced air drying oven for pre-oxidation for 2 hours; Step 6: The pre-oxidized product obtained in step 4 was heated to 700°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept at this temperature for 0.5h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain (FeCo) 3.5 Ni3 / C metal doped carbon nanofibers.

[0035] Embodiment 8 The metal-doped carbon nanofiber absorbing composite material of this embodiment has a molecular formula of (FeCo)4Ni2 / C and is prepared by electrospinning and calcining: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 1.0 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate, including 0.004 mol Fe(NO3)3·9H2O, 0.004 mol Co(NO3)2·6H2O and 0.002 mol Ni(NO3)2·6H2O, is weighed and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 45°C, the maximum humidity is 63% RH, the minimum humidity is 23% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 15 kV, and a distance of 10 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 70°C to dry for 15 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 180°C forced air drying oven for pre-oxidation for 2 hours; Step 6: Heat the pre-oxidation product obtained in step 4 to 900°C at a heating rate of 2°C / min under a nitrogen atmosphere and keep it at that temperature for 1 hour, and then cool it to room temperature at a cooling rate of 5°C / min to obtain (FeCo)4Ni2 / C metal-doped carbon nanofibers.

[0036] The (FeCo)8Ni2 / C metal-doped carbon nanofibers prepared in this embodiment were mixed with paraffin in a mass ratio of 3:7 and pressed into a ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a thickness of about 2 mm. The reflection loss test of the electromagnetic wave frequency band 2~18 GHz was carried out using a vector network analyzer coaxial line method.

[0037] Embodiment 9 The molecular formula of the metal-doped carbon nanofiber absorbing composite material of this embodiment is (FeCo): 4.5 Ni1 / C, prepared by electrospinning and calcination: Step 1: Weigh 0.5 g polyvinylpyrrolidone K30 and 1.0 g polyvinylpyrrolidone K88-96, dissolve in 10 ml DMF, and heat and stir at 40 °C for 3 h; Step 2: According to the above chemical formula, each atomic ratio is converted into a mass ratio, and a total of 0.01 mol of nitrate is weighed, including 0.0045 mol Fe(NO3)3·9H2O, 0.0045 mol Co(NO3)2·6H2O and 0.001 mol Ni(NO3)2·6H2O, and dissolved in the precursor sol obtained in step 1, and heated and stirred at 40°C for 24 hours; Step 3: The metal precursor solution obtained in step 2 is loaded into a 20 ml threaded syringe, the temperature is set to 45°C, the maximum humidity is 63% RH, the minimum humidity is 23% RH, and spinning is performed at an injection rate of 0.5 ml / h, a voltage of 15 kV, and a distance of 10 cm; Step 4: tear off the fiber membrane obtained in step 3 and put it into a vacuum oven at 70°C to dry for 15 hours; Step 5: Move the dried fiber membrane obtained in step 4 into a 180°C forced air drying oven for pre-oxidation for 2 hours; Step 6: The pre-oxidized product obtained in step 4 was heated to 800°C at a heating rate of 2°C / min under a nitrogen atmosphere and kept at this temperature for 2h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain (FeCo) 4.5 Ni1 / C metal-doped carbon nanofibers.

[0038] The products of Examples 1 to 9 were subjected to XRD tests respectively, and the test results are as follows: Figure 1 As shown in the figure, the position corresponding to the standard card of Ni3Fe (ICDD: #88-1715) and the standard card of FeCo (ICDD: #49-1567) is consistent, and the peak at 26° is amorphous carbon. No other characteristic peaks are seen in the figure, indicating that ternary iron-cobalt-nickel alloy doped carbon nanofibers with different proportions were prepared under this experimental condition.

[0039] Depend on Figure 2~3 It can be seen that the metal-doped carbon nanofibers prepared according to the method provided in the present application have the characteristic of good wave absorbing performance.

[0040] Therefore, the present invention adopts a metal-doped carbon nanofiber absorbing material with the above structure and its preparation method and application, which improves the catalytic efficiency of water electrolysis by promoting the rearrangement of the electronic structure at the heterogeneous interface and optimizing the adsorption energy of the intermediate. It has a short preparation cycle, good controllability, and exhibits good stability in seawater.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A metal-doped carbon nanofiber absorbing material, characterized in that: The chemical formula of metal-doped carbon nanofiber absorber is: , where 0 <n<10。 2. The metal-doped carbon nanofiber absorbing material according to claim 1, characterized in that: The maximum reflection loss of the metal-doped carbon nanofiber absorbing material is -10 to -60 dB, and the effective absorption bandwidth is 2 to 7 GHz.

3. The metal-doped carbon nanofiber absorbing material according to claim 1, characterized in that: The metal-doped carbon nanofiber absorbing material has a nano-scale uniform three-dimensional conductive fiber network structure.

4. A method for preparing a metal-doped carbon nanofiber absorbing material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing metal salts in proportion, adding them into an organic solvent containing a high molecular weight polymer, and stirring them uniformly to obtain a precursor solution; S2, spinning the precursor solution by electrospinning to obtain precursor fibers; S3. The precursor fiber is vacuum dried and pre-oxidized in an oven to obtain a stable three-dimensional network fiber structure; the pre-oxidized product is heat-treated in a nitrogen atmosphere to obtain a metal-doped carbon nano-absorbing fiber material.

5. The method for preparing a metal-doped carbon nanofiber absorbing material according to claim 4, characterized in that: In step S1, the metal salt is an iron salt, a cobalt salt and a nickel salt, the iron salt is any one of iron nitrate, iron carbonate and iron acetylacetonate, the cobalt salt is any one of cobalt nitrate, cobalt carbonate and cobalt acetylacetonate, the nickel salt is any one of nickel nitrate, nickel carbonate and nickel acetylacetonate, and the input molar ratio of the iron salt, the cobalt salt and the nickel salt is , where 0 <n<10; The high molecular polymer is any one of polyvinyl pyrrolidone, polyacrylonitrile and polyvinyl alcohol; and the organic solvent is N,N-dimethylformamide or tetrahydrofuran.

6. The method for preparing a metal-doped carbon nanofiber absorbing material according to claim 5, characterized in that: In step S1, the mass ratio of the total mass of the metal salt to the high molecular polymer is (2-3.5):1; the mass ratio of the high molecular polymer to the organic solvent is (1-1.5):

10.

7. The method for preparing a metal-doped carbon nanofiber absorbing material according to claim 4, characterized in that: In step S2, the equipment parameters of the electrospinning method are: voltage intensity 15~20kV, injection rate 0.5ml / h, collector distance 5~15cm, temperature 30~50℃, maximum humidity 60~70%RH, and minimum humidity 20~30%RH.

8. The method for preparing a metal-doped carbon nanofiber absorbing material according to claim 4, characterized in that: In step S3, the vacuum drying temperature is 60-90°C, the insulation time is 8-18h, the pre-oxidation temperature is 120-200°C, and the insulation time is 1-4h.

9. The method for preparing a metal-doped carbon nanofiber absorbing material according to claim 4, characterized in that: In step S3, the heat treatment temperature can be selected from 700 to 900° C., and the insulation time can be selected from 0.5 to 2 h.

10. An application of a metal-doped carbon nanofiber absorbing material as claimed in any one of claims 1 to 3, characterized in that: Used in electromagnetic wave absorbing materials.

Citation Information

Patent Citations

  • Cobalt-nickel alloy-carbon nanofiber epoxy resin wave-absorbing material and preparation method thereof

    CN111548601A

  • Method for preparing electromagnetic wave absorption material from hydrotalcite-based composite nanofiber

    CN111850821A

  • Magnetic ferrite carbon-based nanofiber wave-absorbing material, preparation method and application

    CN113026148A

  • Fe-Ni alloy modified porous carbon fiber composite epoxy resin material and preparation method thereof

    CN114133827A

  • Preparation method of self-supporting iron-nickel alloy decorated nitrogen-doped porous carbon nanofiber lithium metal negative electrode framework material

    CN114388769A

Cited By

  • Three-dimensional spiral carbon nanofiber and preparation method and wave absorbing application thereof

    CN120700614A